Fungal Diseases of Soybeans - Shavkat kyzy, Pirnazarova Makhzuna; Elmurod, Umurzakov (American Journal of Biomedicine and Pharmacy, 2025)
The article provides information about the biological characteristics, distribution, development and reproduction of diseases root rot, stem rot, black rot and brown rot. It also emphasizes the negative impact of diseases on the quantity and quality of harvest.